GENEALOGY OF THE "PUBLIC GOOD" - PROBLEMS AND SHORTCOMINGS. Part 2 - Markova, Ilinida (E-Journal VFU, 2025)
In the article attempts to fix the most basic problematic points arising from the shortcomings of the modern phrase "public good". The autor examines the reasons for the existing social phenomena gravitating around this phrase, whose presence should not satisfy the modern man, but motivate him to rethink his intellectual presence and, consequently, his attitude towards himself and his world.
Keywords: „Public good”; subjectivity; universality; value